Relevancia del uso del sistema de posicionamiento global (GPS) en la agricultura - Leon Briones, Tania Liseth (2022)
This document dealt with the importance of the use of the global positioning system (GPS) in agriculture. Describe the primary benefits and their effectiveness. Agriculture is considered a challenge where every day there is more innovation to cover the different needs required by the agricultural market. The use of new technologies helps to produce more in a limited space, optimizing production and reducing product losses, as well as improving production costs. The Global Positioning System (GPS) allows for precise estimates of position, speed and time. Allowing the collection of data in real time and 24 hours a day, many farmers begin to use products derived from GPS with the aim of improving operations in their agricultural activities, achieving different benefits such as; Less wear and tear on machinery, decreased fuel consumption, decreased costs of inputs such as fertilizers, seeds and agrochemicals, in addition, it allows constant monitoring of the crop that helps detect the presence of diseases or nutritional deficiencies in time and plan production parameters. .